2019
DOI: 10.1038/s41467-019-12305-3
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystal superlattices as phonon-engineered solids and acoustic metamaterials

Abstract: Phonon engineering of solids enables the creation of materials with tailored heat-transfer properties, controlled elastic and acoustic vibration propagation, and custom phonon–electron and phonon–photon interactions. These can be leveraged for energy transport, harvesting, or isolation applications and in the creation of novel phonon-based devices, including photoacoustic systems and phonon-communication networks. Here we introduce nanocrystal superlattices as a platform for phonon engineering. Using a combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…The NC surface and its ligands thus have a significant effect on how NCs are processed (e.g., their solvation, stability in solution, and assembly from colloidal form into solids) , and on their functionality (e.g., their catalytic, electronic, optical, phononic, and thermal performance). For example, for NCs used in catalysis, the surface ligands can impact the catalyst energy efficiency and selectivity. In the case of (opto)­electronics, the type of ligand as well as its orientation determines the surface electrical dipole of individual NCs. This tunes the energy position of the electronic states of individual NCs as well as their assemblies and thus optical absorption and emission. , Furthermore, the electronic transport properties of NC solids depend on the electronic wave function confinement of individual NCs as well as the NC packing in the NC solid (facet-to-facet alignment and spacing), all of which are determined by the ligands. , Mechanical, phononic, and thermal conductivity of solids assembled from NCs are governed by the number of ligand interconnections, their orientation, and the elasticity. These examples illustrate the importance of ligands in optimizing the performance of NCs and NC thin films for different applications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The NC surface and its ligands thus have a significant effect on how NCs are processed (e.g., their solvation, stability in solution, and assembly from colloidal form into solids) , and on their functionality (e.g., their catalytic, electronic, optical, phononic, and thermal performance). For example, for NCs used in catalysis, the surface ligands can impact the catalyst energy efficiency and selectivity. In the case of (opto)­electronics, the type of ligand as well as its orientation determines the surface electrical dipole of individual NCs. This tunes the energy position of the electronic states of individual NCs as well as their assemblies and thus optical absorption and emission. , Furthermore, the electronic transport properties of NC solids depend on the electronic wave function confinement of individual NCs as well as the NC packing in the NC solid (facet-to-facet alignment and spacing), all of which are determined by the ligands. , Mechanical, phononic, and thermal conductivity of solids assembled from NCs are governed by the number of ligand interconnections, their orientation, and the elasticity. These examples illustrate the importance of ligands in optimizing the performance of NCs and NC thin films for different applications.…”
mentioning
confidence: 99%
“…Information on the crystal structure is contained in elastic scattering, for which there is no energy transfer, S ( Q , E = 0) . Inelastic neutron scattering (INS) spectra have been used to obtain information on a number of vibrational processes in NCs, ranging from interparticle vibrations to soft surface modes, and phonons in the nanocrystal core. , Scattering centered around the elastic line at a low energy transfer of micro- to millielectronvolts is referred to as quasi-elastic neutron scattering (QENS). To date, sparsely used for studying ligands on NCs, it probes the individual, diffusive motion of atoms (in this case hydrogen) and can thus be used to develop and validate models for ligand dynamics.…”
mentioning
confidence: 99%
“…In the specific case of neurons, exosomes are released from post-synaptic soma or dendrites [ 24 ], and they mediate several processes, such as the maintenance of homeostasis by triggering synapse pruning by microglial cells [ 30 ], or the outflow of molecular information to neighboring cells, mediated by miRNAs. These miRNAs may induce gene expression in recipient cells in an activity-dependent manner [ 31 ]; as previously described, miR-124 internalized by astrocytes is capable of regulating the glutamate transporter (GLT1) levels, as well as glutamate uptake in the brain [ 23 ].…”
Section: Evs Mediate Communication In Cns—during and Post-developmmentioning
confidence: 99%
“…In a more recent breakthrough, Men et al have demonstrated that the miRNA profile of secreted exosomes is different from the one observed in live neuronal cells [ 24 ]. By generating a cell-type-specific ILVs/exosome reporter (CD63-GFPf/f) in mice, the authors observed that an undescribed neuron-specific miRNA, miR-124-3p, was internalized into astrocytes, also upregulating the glutamate transporter GLT1 [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Organic-molecules-adsorbed cubic nanoparticles have been assembled to form nanoparticle bilayers and show tandem catalytic properties. 13 Superlattices of molecule-adsorbed nanoparticles have been investigated as optical, 14 phonon-engineering, 15 and lithium-ion storage materials, 16 owing to the nano scale periodicity.…”
Section: Introductionmentioning
confidence: 99%